2019
DOI: 10.1002/ptr.6488
|View full text |Cite
|
Sign up to set email alerts
|

Panax notoginseng saponins suppress lipopolysaccharide‐induced barrier disruption and monocyte adhesion on bEnd.3 cells via the opposite modulation of Nrf2 antioxidant and NF‐κB inflammatory pathways

Abstract: Dysfunction of the blood‐brain barrier (BBB) is a prerequisite for the pathogenesis of many cerebral diseases. Oxidative stress and inflammation are well‐known factors accounting for BBB injury. Panax notoginseng saponins (PNS), a clinical commonly used drug against cerebrovascular disease, possess efficient antioxidant and anti‐inflammatory activity. In the present study, the protective effects of PNS on lipopolysaccharide (LPS)‐insulted cerebral microvascular endothelial cells (bEnd.3) were assessed and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 44 publications
2
20
0
Order By: Relevance
“…These findings suggested that 25-OH-PPD was beneficial for the treatment of DM by reversing the complications of DMCM. This finding was consistent with a previous study that used diabetic rats in the presence of PPD and characterized the levels of collagen accumulation and the induction of cardiac hypertrophy and remodeling (11). DMCM is a major complication of DM and can induce cardiac dysfunction (dysfunction of sugar and fat metabolism) in diabetic patients (20).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings suggested that 25-OH-PPD was beneficial for the treatment of DM by reversing the complications of DMCM. This finding was consistent with a previous study that used diabetic rats in the presence of PPD and characterized the levels of collagen accumulation and the induction of cardiac hypertrophy and remodeling (11). DMCM is a major complication of DM and can induce cardiac dysfunction (dysfunction of sugar and fat metabolism) in diabetic patients (20).…”
Section: Discussionsupporting
confidence: 92%
“…PNS is a widely used traditional Chinese medicine extracted from the Sanqi or Tianqi plants. This agent exhibits a wide range of pharmacological and biochemical effects and can be used to treat specific diseases, such as cardiovascular and inflammatory disease, bleeding or pain due to injury, as well as trauma (11). Several chemical compounds and active ingredients have been isolated from PNS, including saponins, flavonoids and cyclopeptides.…”
Section: Introductionmentioning
confidence: 99%
“…Ginsenoside Re enhanced the activation of Nrf2 in Aβ-induced SH-SY5Y cells [76]. The activation of the Nrf2-HO-1 pathway for M2 macrophage polarization is also supported by the findings that a red ginseng-derived saponin fraction suppressed inflammatory responses via the Nrf2-HO-1 pathway in an adipocyte-macrophage co-culture system [42], and that saponins from Panax notoginseng acted as an extrinsic regulator that activates the Nrf2 antioxidant defense system and inhibits NF-κB inflammatory signaling to attenuate LPS-induced monocyte adhesion on cerebral endothelial cells [77].…”
Section: Perspectivementioning
confidence: 70%
“…This extract ameliorated doxorubicin-induced chronic heart failure by inhibiting oxidative stress in rat model. Hu et al [ 37 ] also observed antioxidantive potential of P. notogineng saponins.…”
Section: Discussionmentioning
confidence: 97%